An Integrated Transcriptome Analysis Reveals IGFBP7 Upregulation in Vasculature in Traumatic Brain Injury - Wang, Jianhao; Deng, Xiangyi; Xie, Yuan; Tang, Jiefu; Zhou, Ziwei; Yang, Fan; He, Qiyuan; Cao, Qingze; Zhang, Lei; He, Liqun (Frontiers in Genetics, 2021)
Vasculature plays critical roles in pathogenesis and neurological repair of traumatic brain injury (TBI). However, how vascular endothelial cells respond to TBI at molecular level has not been systematically reviewed. Here, by integrating three transcriptome datasets including whole cortex of mouse brain, FACS-sorted mouse brain endothelial cells and single cell sequencing of mouse brain hippocampus, we revealed the key molecular alteration of endothelial cells characterized by increased Myc targets and Epithelial-Mesenchymal Transition signatures. In addition, immunofluorescence staining of patients’ samples confirmed that IGFBP7 was up-regulated in vasculature in response to TBI. TGFβ1, mainly derived from microglia and endothelial cells, sufficiently induces IGFBP7 expression in cultured endothelial cells, and is significantly upregulated in response to TBI. Our results identified IGFBP7 as a potential biomarker of vasculature in response to TBI, and indicate that TGFβ signaling may contribute to upregulation of IGFBP7 in the vasculature.